PENGARUH DEVIDEN, KEBIJAKAN HUTANG, PROFITABILITAS TERHADAP NILAI PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Dini, Siti; Sibaran, Iin Octavia; Sitorus, Oktorina Maria M.; Tarigan, Dika Ayu Pratiwi Br; Simbolon, Devi (2020)
This study aims to examine the effect of dividends partially and simultaneously, debt policy and profitability with firm value. Where the independent variables in this study are dividends, debt policy, and profitability, while the dependent variable is firm value. This study has a population of 48 mining companies from all sectors. The sample used is secondary data originating from the financial statements of mining companies listed on the Indonesia Stock Exchange. The classic assumption test in this study includes the normality test, multicolonierity test, heteroscedasticity test, autocoleration test, and Glejser test. This data analysis uses test (t), test (f), and coefficient of determination test. The analysis of this data uses SPSS 25. The results of this study indicate that partially the dividend variable and the profitability variable (ROA) have a negative and insignificant effect on firm value (PBV), while simultaneously the debt policy variable (DER) has no and insignificant effect. to the company value (PBV) of mining companies listed on the Indonesia Stock Exchange.